An Octet-Truss Engineered Concrete (OTEC) for lightweight structures. (1st January 2019) - Aghdasi, Parham; Williams, Ian D.; Salazar, Brian; Panditi, Nicole; Taylor, Hayden K.; Ostertag, Claudia P.
Abstract: Recent advances in the development of Ultra-High Performance Fiber-Reinforced Concrete (UHP-FRC) with very high compressive strength has inspired the development of a lightweight structure by engineering the void spaces in the material, thus taking advantage of porous concrete's thermal insulating properties while maintaining strength and stiffness. This paper refers to this engineered material as Octet-Truss Engineered Concrete (OTEC). To make OTEC structures, UHP-FRC and "green" UHP-FRC (G-UHP-FRC) mixtures were developed. 50.8-mm side-length OTEC unit cell specimens with various element diameters as well as 5 × 1 × 1-cell OTEC flexural specimens with 8 mm-diameter elements were cast and tested under uniaxial compression and four-point bending, respectively. The compressive strength of the OTEC unit cell specimens with various element diameters is mainly stretching-dominated, and hence considerably surpasses that of the control foam Green Ultra-High Performance Concrete specimens with random pore orientations. These results indicate a promising application of UHP-FRC and G-UHP-FRC OTECs for lightweight structures.